Generating Interest in Literacy Through Project-Based Learning in Pancoran: An Action Service Initiative - Julia Frances Lonan; Deshinta Puspa Ayu Dwi Argaswari; Kenny Fernando; Giovanni Richard Halim; Anindita Aulia Jasmine; Gabriele Teresa Budiarto; Megan Leigh Abraham; Celine Arielle Sente; Michelle Christabel; Rojan Mejia Abenoja; Peace Yemima (Journal of Community Services: Sustainability and Empowerment, 2025)
Literacy is a critical issue to tackle in Indonesia. Hence, to alleviate it, Kampung Literasi Pancoran has been developed to help residents of the Pancoran ward, helping elementary students and adults alike to improve their literacy skills in multiple aspects by garnering their interest through project-based learning. English literacy is offered to elementary students using multiple mediums, while financial literacy is taught to adults. This study implements an action research cycle, where constant improvements were made throughout the 9 week period. Findings show that more students participated and had positive sentiments to the lessons prepared, while more attention needed to be brought to ensure full community support and social progress for all stakeholders.